Performance Analysis of Plastic Bottle Crushing Machine with Electric Motor Drive - Rinasa Agistya Anugrah; Zuhri Nurisna; Fandi Widiyanto; Aziz Abdul Latif (Proklamasi 45 University, 2020)
Garbage is now very possible to be recycled. One way to help the recycling process is to make a plastic bottle crushing machine. In this study,the test material is a plastic bottle with a thickness of 0.1 mm. Then we calculated the engine capacity, electrical energy, the profit of production costs, the comparison of the efficiency of the electric motor drive compared to the gasoline engine drive, the rotation of the blade, and linear velocity v-belt. This study's results were that the smaller modifiedmachinescould crush plastic bottles into crushed plastic with a length smaller than 20 mm as much as 27.93 kg/hour. The comparison efficiency of using a plastic bottle crushing machine with an electricmotor drive witha gasoline motor drive is 2.6:1. It can be concluded that the plastic bottle crushing machine with an electric motor drive is superior to those witha gasoline engine drive.